Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank Syariah - Nur Mawaddah (Faculty of Economic and Business, 2015)
The Determinant That Affect The Profitability in Islamic BanksThe aim of this study are to analyze the direct effect of financing and net interest margin to return on asset, and indirect effect of financing and net interest margin into return on asset. The independent variables in this study are financing and net interest margin, the dependent variable is return on asset, and intervening variable is non performing financing (NPF). The method that used in this study is path analysis. The result shown that the financing has direct effect to return on asset 2.45% and net interest margin has direct effect to return on asset 6.45%. Non performing financing has direct effect to return on asset 4.32%. Financing has indirect effect to non performing financing 2.77%. Net interest margin has indirect effect on non performing financing 2.77%.DOI: 10.15408/etk.v14i2.2273